Healthy and Productive Villages: Utilization Local Technology for Organic Waste Management - Maziyya, Nur; Rahayuwati, Laili; Pramukti, Iqbal; Luthfi, Wazirul; Agustina, Habsyah Saparidah; Ibrahim, Kusman; Lukman, Mamat; Witdiawati, Witidiawati (Media Karya Kesehatan, 2025)
Waste management has become a crucial environmental issue as an increase of waste volume due to population growth and rapid urbanization. Lack of effective waste management can have an impact not only on polluting the environment, but can also threaten public health. Therefore, it is important to implement effective waste management to prevent environmental damage caused by waste. This Community Service aims to increase the ability and active role of the community in managing household waste through the establishment of a Healthy Productive Village program. This activity was carried out through several stages and a series of activities including socialization, demonstrations and training on household waste processing for 13 cadres and also 15 assisted families. The results of the service showed that participants knew and were able to sort waste based on its type, namely organic and inorganic, the formation of fostered families who were able to implement waste sorting and the creation of eco enzymes and hand washing soap from processing household waste. The result of this activity, namely the Healthy Productive Village Program, is expected to be a program that is not only implemented in Compreng village but also in other villages and districts in Indonesia to overcome the waste problem with effective and economically valuable waste management. Keyword: Productive healthy village, eco enzyme, waste management.